Histopathological assessment of lymph nodes in upper gastrointestinal cancer: does triple levelling detect significantly more metastases?. Issue 11 (13th February 2007) - McGrath, Stephen; Cross, Sarah; Pritchard, Susan Anne
Abstract : Background: For cancers of the upper gastrointestinal tract it is standard to examine one section/level, from paraffin blocks containing lymph node tissue, for metastatic tumour. Aims: To determine whether significantly more metastases can be detected by assessing two additional levels. Methods: 101 archival upper gastrointestinal cancers were evaluated. All negative lymph nodes were examined at two additional levels separated by 100 μm and stained by H&E. The slides were examined for the presence of metastases. Results: 1143 lymph nodes, that were originally clear of metastases, were examined at a further two levels (three levels in total); 23 additional metastases were identified in 17 patients. Eleven of these patients were already stage N1 before examination of the additional levels. However, six patients were originally N0, and were therefore upgraded to N1. Conclusions: Examining lymph nodes at three levels did detect more metastatic deposits than examination of one section/level. In six patients this changed the N stage from N0 to N1. This would have significant prognostic and management implications.